What Explains Movements in the Peso/Dollar Exchange Rate? - Wu, Yi (IMF Working Papers; Working Paper, 2013)
This paper examines the factors affecting the weekly peso/dollar exchange rate movements between 1999 and 2013 using an error correction model. The model fits the historical data well. While copper price is the most important determinant of the peso exchange rate over the long run, other factors including interest rate differential, global financial distress, local pension funds' derivative position, as well as the Federal Reserve's quantitative easing also affect the peso in the short run. The Central Bank of Chile's foreign exchange interventions in 2008 and 2011 had a small impact on the peso.